Direct effects of octreotide on osteoblast cell proliferation and function - Vitali, E.; Palagano, E.; Schiavone, M. L.; Mantovani, G.; Sobacchi, C.; Mazziotti, G.; Lania, A. (Journal of endocrinological investigation, 2022)
Purpose Octreotide (OCT) is a first-generation somatostatin analog (SSA) used in the treatment of acromegaly and neuroendocrine tumors (NETs). In both diseases, OCT interacts with somatostatin receptors 2 and 5 (SSTR2 and SSTR5), inhibiting hormone hypersecretion and cell proliferation. Skeletal health is an important clinical concern in acromegaly and NETs, since acromegalic osteopathy and NET bone metastasis occur in a remarkable number of patients. While OCT’s effect on NET and pituitary cells has been extensively investigated, its direct action on bone cells remains unknown. Methods Here, we investigated OCT direct effects on cell proliferation, differentiation, mineralization, and chemoattractant capacity of murine primary osteoblasts and osteoblast cell line MC3T3-E1. Results OCT inhibited osteoblasts and MC3T3-E1 cell proliferation (− 30 ± 16%, and − 22 ± 4%, both p < 0.05 vs control) and increased MC3T3-E1 cell apoptosis (+ 76 ± 32%, p < 0.05 vs control). The anti-proliferative action of OCT was mediated by SSTR2 and SSTR5 in MC3T3-E1, while its pro-apoptotic effect was abrogated in SSTR2-silenced cells. The analysis of genes related to the early and late phases of osteoblast differentiation showed that OCT did not affect Alp, Runx2 , Bglap, Spp1, and Sost levels in MC3T3-E1 cells. Similarly, OCT did not affect ALP activity, mineralization, and osteoclastogenic induction. Finally, Vegfa expression decreased in OCT-treated MC3T3-E1 cells and OCT inhibited pancreatic NET cell migration toward the osteoblast-conditioned medium. Conclusion This study provides the first evidence of the direct action of OCT on osteoblasts which may have clinically relevant implications for the management of skeletal health in subjects with acromegaly and metastatic NETs.